The Church in Wales and the State: A Juridical Perspective - Doe, Norman (Journal of Anglican studies, 2004)
In 1536 Wales (Cymru) and England were formally united by an Act of Union of the English Parliament. At the English Reformation, the established Church of England possessed four dioceses in Wales, part of the Canterbury Province. In 1920 Parliament disestablished the Church of England in Wales. The Welsh Church Act 1914 terminated the royal supremacy and appointment of bishops, the coercive jurisdiction of the church courts, and pre-1920 ecclesiastical law, applicable to the Church of England, ceased to exist as part of public law in Wales. The statute freed the Church in Wales (Yr Eglwys yng Nghymru) to establish its own domestic system of government and law, the latter located in its Constitution, pre-1920 ecclesiastical law (which still applies to the church unless altered by it), elements of the 1603 Canons Ecclesiastical and even pre-Reformation Roman canon law. The Church in Wales is also subject to State law, including that of the National Assembly for Wales. Indeed, civil laws on marriage and burial apply to the church, surviving as vestiges of establishment. Under civil law, the domestic law of the church, a voluntary association, binds its members as a matter of contract enforceable, in prescribed circumstances, in State courts.